ANALYSIS OF MINING, AGRICULTURE AND SERVICES SECTORS AS LEADING ECONOMIC SECTORS IN BANYUWANGI DISTRICT - Ali Asyhar; Stevanus Gatot Supriyadi (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to analyze various leading sectors in Banyuwangi district to be developed in order to increase regional economic growth. This research uses a qualitative approach with more emphasis on the qualitative form of literature, namely the main source from the Banyuwangi Regency Central Bureau of Statistics. The data analysis tools used are LQ, DLQ and Shift Share and the research results obtained show that in Banyuwangi Regency the most superior sector is the Education sector, namely obtaining average data of 2.02, the Electricity Procurement Sector and the Education Services Sector in Banyuwangi Regency have a very large role, this can be seen in the contribution of Electricity Procurement and the Education Services Sector to the GRDP of Banyuwangi Regency. The magnitude of the sector's contribution can be seen in the average contribution figures from 2018 to 2022 with values ​​of 2.00 and 2.02. while the Mining and Quarrying Sector, electricity and gas procurement, transportation and warehousing, accommodation provision, information and communication, financial and insurance services, real estate, government administration are sectors that are included in the Potential category.